COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN KAWASAN EKONOMI KHUSUS - Elsa Trisniati; Juliannes Cadith; Kandung Sapto Nugroho (Jurnal Governansi, 2022)
Tourism is a large sector that includes many things in it. Facilities and infrastructure that can support the life of the tourism sector are not only owned by one party, but involve various stakeholders so that collaboration between these stakeholders is needed to collaborate, but collaborative governance in the development of the Tanjung Lesung Special Economic Zone is still not optimal. The purpose of this study was to determine and analyze collaborative governance in the development of the Tanjung Lesung SEZ. This research is based on the Collaborative Governance Theory from Ansell and Gash. This theory is to examine the collaboration process which includes dimensions including the collaboration process, initial conditions, institutional design, and facilitative leadership. The research method used is a qualitative method with a descriptive approach. Because the main purpose of this study is to describe and provide an explanation of collaborative governance in the development of the Tanjung Lesung SEZ. Informants were determined by purposive sampling and snowball techniques. The data collection technique used is by conducting observations, interviews, literature studies and documentation. The result of this research is that Collaborative Governance in the development of the Tanjung Lesung SEZ has not been implemented optimally. Suggestions from this research are that the community increases its resources so that they can collaborate, the government provides ongoing training to help the community actively collaborate and the government forms a special forum as a forum to communicate and discuss the vision and mission to be achieved together.